A Selection of Barrier Factors Affecting Reverse Logistics Performance of Thai Electronic Industry - Tossapol Kiatcharoenpol; Pornwasin Sirisawat (My University, 2020)
The aim of research is to identify and select various significant barriers affecting Reverse Logistics (RL) performance in Thai Electronic Industry.The work utilizes Structure Equation Modeling (SEM) to empirically validate the relation of barrier to RL performance based on path analysis and Confirmation Factor Analysis (CFA) of SEM.The questionnaire to investigate barriers and RL performance are developed by using a literature review of international research works.The survey has been carried out on mostly large and medium size electronic companies with running operations more than 10 years and located in Thailand.The 67 responses can be obtained and formulate the SEM model for testing and analysis.The hypotheses were tested in which Barriers was directly, indirectly negatively associated with RL performance.After the modification of SEM model according to fit indices, it was shown that 29 barriers are found statistically significant in this empirically study.These barriers can be categorized into eight groups.Such barriers are Management barrier, Organization barrier, Product barrier, Technological barrier, Infrastructural barrier, Financial barrier, Involvement and Support barrier and Legal barrier.The research finding gives priority to enhancement in RL practices in electronic industry to establish effective RL projects as a crucial strategy to meet the environment awareness in global trends.
Keywords: Sustainable Supply Chain Management